The Ponseti Method vs. Surgical Treatment for Idiopathic Clubfoot: A Prospective Long-Term Follow-Up - Martin Svehlik; Bernhard Guggenberger; Michael Stöckler; Sebastian Klim; Tanja Kraus (Children)
Background: Idiopathic clubfoot is a common skeletal deformity in newborns that can cause functional limitations, pain, and reduced quality of life. The Ponseti method has become the gold standard for clubfoot treatment, replacing previous extensive surgical approaches. However, there is a lack of prospective long-term data comparing surgical and Ponseti treatments. Methods: This is a follow-up on a single-center, prospective, randomized clinical trial that started in 2001. The aim of this study was to compare the Ponseti method with surgical treatment. The current report presents the long-term results at adulthood of 12 clubfeet (9 subjects) in the Ponseti group and 9 clubfeet (5 subjects) in the surgical group. The evaluation included morphology, function, and quality of life, which were assessed through gait analysis, X-rays, and standardized questionnaires (FRS, ICFSG, AOFAS, SF-36). A Functional Rating System for clubfeet was defined as the primary outcome. Results: The Ponseti group had higher Functional Rating System scores, better ankle dorsiflexion mobility, and lower pain levels. Additionally, they reported better quality of life according to the Short Form 36 survey. However, neither group achieved radiographically normal foot morphology. Conclusions: The 18-year follow-up results indicate that the Ponseti method produces superior outcomes in terms of mobility, gait, function, and quality of life when compared to surgically treated feet, despite the presence of persistent morphological deviations.